Mutagenesis of the Tal Gene-Encoding Transaldolase in the Cyanobacterium, Anabaena Sp. PCC7120 - Karakaya, H.; Mann, N.H. (My University, 2008)
The transaldolase gene (tal) of Anabaena sp. PCC7120 was interrupted by the insertion of the interposon Ω. Transaldolase assays showed that the tal mutant strain possessed the same activity as the wild-type, indicating that the second copy of the gene complements the enzyme activity. Being coded by a gene (zwf) downstream of tal and probably in the same operon, glucose-6-phosphate dehydrogenase (G6PDH) activity was also analysed. Only 34% of wild-type G6PDH activity was retained in the tal mutant strain. This may have due to the polar affect of tal mutation on the transcription of the zwf gene. Growth of the tal mutant was not different than that of the wild-type in the presence of combined nitrogen, but the mutant reached the stationary phase faster than the wild-type in the absence of combined nitrogen. This was probably because of the reduction of G6PDH activity, resulting in less production of reductant and energy in heterocysts, which negatively affects nitrogen fixation and growth. © TÜBİTAK.
Keywords: Anabaena; Glucose-6-Phosphate Dehydrogenase; Tal Mutation; Transaldolase Mutant